MULTIVARIATE LOGISTIC MODEL OF HOSPITAL LENGTH OF STAY CLINICAL PREDICTORS AFTER APPENDECTOMY: Multivariate Logistic Model Of Length Of Stay After Appendectomy - Doklestić, Krstina S; Lončar, Zlatibor; Bukumirić, Zoran (Medical Research, 2022)
Background Appendectomies are interesting because they are the most common emergency abdominal operations, they are considered a simple procedure, and imperative is a quick recovery measured by hospital length of stay (LOS). But this is not always the case in clinical practice, hospitalization can be prolonged, and the question is which factors affect it. Methods A multivariant logistic model of LOS predictors analyzed from clinical data of 446 patients who underwent appendectomy at the Clinic for Emergency Surgery, Belgrade. Patients were divided into Short LOS group (SLOS hospital stay ≤3 days, 157 patients) and in Long LOS group (LLOS hospital stay >3 days, 289 patients). Results Significant differences were detected between group SLOS and LLOS in age (p<0.001), comorbidities (p<0.01), preoperative WBC (p = 0.04); preoperative CRP (p < 0.001); peritonitis (p < 0.001), using ≥ 2 antibiotics (p < 0.001), complicated appendicitis (p < 0.001), surgical time (P < 0.01). No significant difference was found concerning gender, postoperative WBC, CRP, and complications (p>0.05). Patients who underwent laparoscopic appendectomy (LAP) had a statistically significantly shorter hospitalization time compared to those who underwent Mini-Incision Open Appendectomy (MIOA) (p < 0.001). Multivariate logistic model found three statistically significant predictors of longer hospitalization: CRP preoperatively (B=0.006, p=0.047), OR=1.006, 95% CI (1.000-1.012), type of surgery (B=1.199; p<0.001), OR=3.3 95% CI (2.074-5.300), complicated appendicitis (B=0.762; p=0.003), OR=2.142, 95% CI (0.284-0.768). Conclusion Surgical approach has statistically the most significant impact on LOS. Laparoscopic appendectomy is superior to Mini-Incision Open Appendectomy concerning the hospital LOS.